2016
DOI: 10.5194/gmd-2016-106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PMIP4-CMIP6: the contribution of the Paleoclimate Modelling Intercomparison Project to CMIP6

Abstract: Abstract.The

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 89 publications
(108 reference statements)
0
52
0
Order By: Relevance
“…One set of such calculations will be performed with a version of the LBLRTM radiative transfer model (Clough et al, 2005) updated to reflect recent changes to the HITRAN spectroscopic database (Rothman et al, 2013). Many of the reference models participating in the intercomparison exercise described by Pincus et al Kageyama et al (2016) (2015) have indicated that they will also provide analogous results. Reference results will be provided for the sets of atmospheric conditions described in the last section -of the order of 2000 profiles for all perturbations.…”
Section: Planned Analyses and Supporting Calculations: Parameterizatimentioning
confidence: 51%
“…One set of such calculations will be performed with a version of the LBLRTM radiative transfer model (Clough et al, 2005) updated to reflect recent changes to the HITRAN spectroscopic database (Rothman et al, 2013). Many of the reference models participating in the intercomparison exercise described by Pincus et al Kageyama et al (2016) (2015) have indicated that they will also provide analogous results. Reference results will be provided for the sets of atmospheric conditions described in the last section -of the order of 2000 profiles for all perturbations.…”
Section: Planned Analyses and Supporting Calculations: Parameterizatimentioning
confidence: 51%
“…PMIP discriminates between the experiments that are endorsed by the World Climate Research Program (WCRP) CMIP6 committee (PMIP4 Tier 1: past1000, Mid Holocene and Last Interglacial, Last Glacial Maximum, and Mid Pliocene Warm Period; see Kageyama et al, 2016) and additional simulations (PMIP4 Tier 2 and Tier 3) that are more tailored to specific interests of the palaeoclimate modelling community. This distinction is motivated by the PMIP3 experience that only a limited number of participating groups were able to afford computational resources for multiple multi-centennial simulations.…”
Section: The Experimentsmentioning
confidence: 99%
“…This paper is part of a suite of five documenting the PMIP contributions to CMIP6. Kageyama et al (2016) provide an overview of the five selected time periods and the experiments. More specific information is given in the contributions for the mid-Holocene (midHolocene) and the previous interglacial (lig127k) by Otto-Bliesner et al (2017), for the last glacial maximum (lgm) by Kageyama et al (2017), and for the mid-Pliocene warm period (midPliocene) by Haywood et al (2016), and the present paper on the last millennium (past1000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the PRISM3D/PlioMIP1, newly archived proxy evidences have been integrated as PRISM4 dataset (Dowsett et al, 2016;hereafter D16) which is planned to be used for an ongoing modelling intercomparison project, PlioMIP phase 2 (PlioMIP2; Haywood et al, 2016b; hereafter H16b), a part project of PMIP4 (Kageyama et al, 2016). In the PRISM4/PlioMIP2, boundary conditions for the Pliocene climate simulations including orography and ice sheets have been updated.…”
Section: Introductionmentioning
confidence: 99%